Voluminous Urethral Stone – A Very Rare Complication After Male Suburethral Sling Surgery As A Result of Sling Erosion Into Proximal Urethra - Scarneciu, Ioan; Andrei, Cristian; Scarneciu, Camelia; Lupu, Aura Mihaela; Bratu, Ovidiu Gabriel; Lupu, Sorin (Urology Journal, 2018)
Male sling for urinary incontinence is usually accompanied by very good results, with a small number of complications, but, when appear, they may be redundant. Voluminous urethral stone developed on suburethral sling as a result of sling erosion into the proximal urethra is an extremely rare complication (following the analysis of cases published on the internet, the authors of this article no longer identified another similar case). We present the case of a patient who presented in our clinic for severe and permanent urinary incontinence, perineal discomfort and pain that was influenced by position. His past medical history showed polytrauma with lumbar fracture and medullary involvement (34 years ago) and transobturator suburethral sling surgery for urinary incontinence about 6 years ago in another urology unit, without relieving symptoms. Imaging investigations have showed a voluminous urethral stone developed on polypropylene sling and another small stones in that area. Stones surgical extraction was performed by perineal approach (together with the mesh), proximal urethra was closed after excision to apparently healthy urethral tissue (to prevent possibility of later severe incontinence) and a permanent suprapubic cystostomy catheter was inserted. Patient is dry at follow-up visits (at 1 and 3 months) and he reported significant improvement in quality of life. The case is spectacular due to the rarity of the complication presented, patient developingurethral erosion without clinical manifestations to suggest this matter (infection or fistula), the symptoms being absent for a long time.